The Bacteriological Quality, Safety, and Antibiogram of Salmonella Isolates from Fresh Meat in Retail Shops of Bahir Dar City, Ethiopia. (25th July 2017) - Azage, Melkamnesh; Kibret, Mulugeta
Abstract : The habit of raw meat consumption in addition to the poor hygienic standards and lack of knowledge contribute to food-borne diseases outbreaks. The objective of this research was to assess the bacterial quality and safety of fresh meat from retail Bahir Dar City, Ethiopia. A total of 30 fresh meat samples were collected from butcher shops. Standard bacteriological methods were used to isolate and enumerate bacteria. Kirby-Bauer disk diffusion method was used for antimicrobial susceptibility testing of Salmonella isolates. The mean counts of AMB, TC, and S. aureus were log10 4.53, 3.97, and 3.88 log10 cfu/g, respectively. Salmonella was isolated from 21 (70%) of the samples. Salmonella isolates in this study were highly susceptible to ciprofloxacin, gentamycin, and norfloxacin while they were resistant to erythromycin and tetracycline. High rate of multiple drug resistance was also noticed in Salmonella isolates. The microbial loads of meat were above the recommended microbial safety limits. Besides this, the isolation rate of Salmonella was high and high levels of drug resistance were documented for Salmonella isolates. Measures on handling and appropriate personal hygiene practices of workers in the retail shops are recommended to reduce the change of forborne disease outbreaks.